Оптичний пінцет : фізичні принципи його роботи та галузі використання - Михайленко, Я. Р. (ХНУРЕ, 2023)
This work is devoted to the study of the physical operation principles of the optical instrument called optical tweezers, which allows to manipulate microscopic objects by means of laser light. The paper discusses the background to the emergence of optical tweezers, the physical principles on which their operation is based and the main types of optical traps used in such instruments. In addition, the main fields of application of optical tweezers are shown, as well as the prospects for their development.